2015
DOI: 10.1186/s12871-016-0227-9
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane and isoflurane inhibit KCl-induced Class II phosphoinositide 3-kinase α subunit mediated vasoconstriction in rat aorta

Abstract: BackgroundClass II phosphoinositide 3-kinase α-isoform (PI3K-C2α) is involved in regulating KCl-induced vascular smooth muscle contraction. The current study was to investigate the effects of sevoflurane (SEVO) and isoflurane (ISO) on KCl-elicited PI3KC2α mediated vasoconstriction in rat aortic smooth muscle.MethodsIsometric force, in the absence or presence of SEVO or ISO (1 ~ 3 minimum alveolar concentration, MAC), PI3K inhibitor LY294002, Rho kinase inhibitor Y27632, and membrane translocation of PI3K-p85, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…ISO also inhibited MLC phosphorylation in response to Ang II, which was associated with a decrease in MYPT1/Thr853 but not CPI-17 phosphorylation [20] . Moreover, we demonstrated that SEVO and ISO can mediate rat aortic vasodilation through the KCl/PI3K-C2α/Rho kinase/MYPT1/MLC pathway [21] . In addition, recent studies have con rmed that SEVO can inhibit the activity of Rho kinase in vascular smooth muscle cells and enhance vasodilation under PI3K inhibition [22] .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…ISO also inhibited MLC phosphorylation in response to Ang II, which was associated with a decrease in MYPT1/Thr853 but not CPI-17 phosphorylation [20] . Moreover, we demonstrated that SEVO and ISO can mediate rat aortic vasodilation through the KCl/PI3K-C2α/Rho kinase/MYPT1/MLC pathway [21] . In addition, recent studies have con rmed that SEVO can inhibit the activity of Rho kinase in vascular smooth muscle cells and enhance vasodilation under PI3K inhibition [22] .…”
Section: Introductionmentioning
confidence: 78%
“…We also demonstrated that SEVO and ISO attenuated KCl (60 mM)-induced arterial contraction in a concentrationdependent manner and that LY294002 (10 mM) and Y27632 (1 µM) also inhibited contraction. The KCl/PI3K-C2α/Rho kinase/MLCP/MLC pathway may mediate the intracellular mechanism of VSM contraction induced by volatile anesthetics [21] . Fujii et al showed that SEVO did not alter the changes in Ca 2+ in aortic cells of diabetic rats induced by NE [23] , and SEVO at clinical concentrations could signi cantly inhibit the response of nondiabetic rats to NE but had no such effect on diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether miRs regulate expression of RhoA/ROK in arterial grafts induced by isoflurane exposure remain unknown. Yang et al [33] demonstrated that Iso inhibit KCl-induced PI3K-C2α-participation, Rho kinase-mediated MLC phosphorylation, and vasoconstriction in rat aortic smooth muscle. Here, our data indicated that isoflurane preconditioning supressed the expression of RhoA/ROK and activated endothelial eNOS, resulting in vasodilation of LIMA, so we demonstrated that isoflurane preconditioning may be very useful for reperfusion of ischemic myocardium after revascularization for left anterior descending coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…PI3Kγ's role in both hypertension and (the often associated) inflammation means inhibitors of this isoform might be attractive therapeutic candidates via both anti‐hypertensive and anti‐inflammatory properties [173,176]. Other Class I PI3K isoforms may also hold roles in hypertension, with p110δ expression being upregulated in aortas of hypertensive rats [177], while Class II PI3KC2α appears to regulate vascular smooth muscle contraction and play a role in spontaneous hypertension in rats via a Ca 2+ ‐PI3KC2α‐RHO axis [178–180].…”
Section: Pi3ks In Other Aspects Of Cardiovascular Diseasementioning
confidence: 99%